Association between oxidative balance score and serum cobalt level in population with metal implants: a cross-sectional study from NHANES 2015–2020 - Yuan, Wenxiu; Chen, Jing; Sun, Jun; Song, Chenyang; Chen, Zhi (Frontiers in Nutrition, 2024)
Background: Growing evidence indicates that metal implants influence the body's oxidative stress status, which in turn affects the degradation and stability of metal implants.The oxidative balance score (OBS) is a composite indicator, reflecting the overall oxidative balance of pro-and antioxidants of the human body. However, the associations between OBS and the level of metal ions on the population with metal implants remain to be elucidated.We conducted a cross-sectional study using data from 2015 to 2020 National Health and Nutrition Examination Survey (NHANES). Dietary and lifestyle factors closely associated with oxidative stress were quantified to calculate the OBS. Weighted multivariate logistic regression and smooth curve fittings were performed to examine the relationship between OBS and serum cobalt levels. Subgroup analyses were stratified by age and gender. In cases where nonlinearity was detected, threshold effects were assessed using a two-piecewise linear regression model.A total of 549 participants were included in this analysis. The dietary OBS was negatively associated with serum cobalt level in fully adjusted model (β=-0.179, 95%CI: -0.358 to -0.001, P: 0.04918). Stratified by age and gender, negative correlation of OBS and dietary OBS with serum cobalt level was observed only in men and age over 70 years participants. Threshold effect analysis showed linear relationships between OBS, dietary OBS and cobalt level in males. There were nonlinear relationships between OBS, dietary OBS and cobalt level in age over 70 years participants, with inflection points identified at 16.3 and 8.7 for OBS and dietary OBS, respectively.Conclusions: Our study confirms the inverse relationships between oxidative stress and serum cobalt level in individuals with metal implants, highlighting the significance of optimizing OBS to mitigate the risk of metal ion toxicity. These findings emphasize the importance of maintaining an antioxidant diet and lifestyle, particularly as they offer greater protective effect for males and the elderly population.